Hatchepsut the female pharaoh - Tyldesley, Joyce A. (London Penguin, 1999)
Queen - or, as she would prefer to be remembered King - Hatchepsut was an astonishing woman. Brilliantly defying tradition she became the female embodiment of a male role, dressing in men's clothes and even wearing a false beard. Forgotten until Egptologists deciphered hieroglyphics in the 1820's, she has since been subject to intense speculation about her actions and motivations. Combining archaeological and historical evidence from a wide range of sources, Joyce Tyldesley's dazzling piece of detection strips away the myths and misconceptions and finally restores the female pharaoh to her rightful place.
Includes bibliographical references (p. [256]-257) and index.
Keywords: Hatshepsut, Queen of Egypt